Marked Response of Rat Ileal and Colonic Microbiota After the Establishment of Alzheimer’s Disease Model With Bilateral Intraventricular Injection of Aβ (1-42) - Xu, Qing; Wen, Lingmiao; Wei, Guihua; Zhao, Xiaoqin; Liu, Yanjun; Xiong, Wei; Zhang, Tinglan; Fan, Yuqing; Chen, Chunlan; Xiang, Chunxiao; Chen, Chang; Chen, Yunhui; et al. (Frontiers in Microbiology, 2022)
Alzheimer’s disease (AD) is a common neurodegenerative disease. More evidence has shown that gut microbiota is closely associated with AD. Also, studies have shown that the distribution of gut microbiota vary in different sections of the intestine. In this study, a rat model of AD was established using a bilateral intraventricular injection of β-amyloid (1-42) (Aβ (1-42)), and the behavior of rats, hippocampal Aβ (1-42) deposition and pathological changes, and the ileal and colonic microbiota in each group were analyzed. We observed that the model rats had obvious memory and cognitive impairment, increased Aβ (1-42) deposition, and hippocampal tissue pathological damage, indicating that the AD model was successfully established. Through 16S rRNA-sequencing analysis, we found that α diversity, β diversity, and dominant microbiota in the ileum and colon of normal rats were significantly different, showing spatial heterogeneity. Additionally, the surgery and injection of Aβ (1-42) caused various degrees of disturbances in the ileal and colonic microbiota of rats. These findings provide new insights for the study of the gut microbiota of AD rats and help advance the development of therapeutic strategies for intervening AD through the gut microbiota.